Detection of nephrotoxic drugs and dose adjustment in patients with low glomerular filtration rate in community pharmacy: A multicenter study in Spanish community pharmacies - Gema Escribá-Martí; Iker Cámara-Ramos; María Teresa Climent-Catalá; Verónica Escudero-Quesada; Luis Salar-Ibáñez (PLoS ONE, 2025)
Chronic kidney disease (CKD) represents a significant global health burden, with its prevalence markedly increasing in the elderly. This multicenter, non-controlled, prospective study was conducted in 16 Spanish community pharmacies to assess the feasibility of identifying potentially inappropriate prescriptions (PIPs) in patients with reduced estimated glomerular filtration rate (eGFR). Patients over 60 years old with a body mass index between 19 and 35 kg/m2, who were taking at least one nephrotoxic medication or a drug requiring dose adjustment based on renal function, were recruited. A point-of-care (POC) test for creatinine using the StatSensor Xpress® analyzer was performed for those lacking an eGFR measurement in the previous three months, with eGFR calculated via the CKD-EPI formula. Of the 670 patients recruited (mean age 72.5 ± 9.3 years; 49.9% female), 455 had an eGFR > 60 ml/min/1.73 m2, while 215 had values below this threshold. The medication of these latter patients was reviewed, and in 90 of them (41.9%) a potentially inappropriate prescription was identified, leading to their referral to their primary care physician. Of the total sample, 13.4% of the patients had at least one PIP. Changes were requested for 9.0% of the medications, and these were implemented in 3.4%. The proportion of PIPs increased with CKD severity, with higher intervention rates observed in advanced stages. These findings highlight the potential of community pharmacies to contribute to early CKD risk detection and medication optimization, emphasizing the need for enhanced direct communication channels between pharmacists and physicians to improve patient outcomes.